A Pyroptosis-Related Signature Predicts Overall Survival and Immunotherapy Responses in Lung Adenocarcinoma - Zhu, Kaibin; Yan, An; Zhou, Fucheng; Zhao, Su; Ning, Jinfeng; Yao, Lei; Shang, Desi; Chen, Lantao (Frontiers in Genetics, 2022)
Background: lung adenocarcinoma (LUAD) is a highly malignant with poor prognosis. Pyroptosis play important role in LUAD. The present study explored the prognostic potential of a pyroptosis related signature in LUAD. Methods: The genomic data of LUAD was from TCGA and GEO databases. The samples were classcified by pyroptosis related genes (PRGs) using K-means clustering. The characteristics of tumor microenvironment between the two subtypes were analyzed. Differentially expressed genes (DEGs) between the two subtypes were identified and functional enrichement analysis and module analysis were performed. A prognostic model was constructed by LASSO Cox regression. It’s prognostic value was evaluated. Results: Genetic and transcriptional changes of PRGs were observed in LUAD. A total of 30 PRGs was differential expressed in LUAD tissues. Patients with LUAD were classified into two subtypes based on PRGs. The subtype 1 has better overall survival than the subtype 2. The two subtypes showed significant different tumor microenvironment characteristics. The subtype 2 was with higher immune infiltration compared with that in the subtype 1. A total of 719 DEGs was identified between the two groups. A co-expression networks was constructed by WGCNA using these DEGs. The modules of the network were analyzed. Subsequently, a prognositic model with 7 genes was constructed, including FOSL1, KRT6A, GPR133, TMPRSS2, PRDM16, SFTPB, and SFTA3. The constructed model was assovciated with overall survival and response to immunotherapy of patients with LUAD. Conclusion: A pyroptosis related signature was constructed for predicting overall survival and responses to immunotherapy in LUAD.